2014
DOI: 10.1200/jco.2014.32.4_suppl.188
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide after failure of docetaxel and abiraterone in metastatic castrate resistant prostate cancer (mCRPC): Results from an expanded access program.

Abstract: 188 Background: Abiraterone or enzalutamide are licensed for use post-docetaxel in metastatic castrate resistant prostate cancer (mCRPC). Both target the androgen receptor signalling pathway. There is little information describing their sequential use. Methods: Patients with mCRPC who had failed treatment with docetaxel and abiraterone received enzalutamide as part of an expanded access program. Patients were reviewed four weekly and post-treatment PSA used to determine efficacy. Results: Twenty three patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A total of 16 retrospective cohort analyses assessed the effectiveness of a second ARAT therapy after progression on prior docetaxel and ARAT treatment (Table 2) [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Enzalutamide was the most investigated agent in this setting (docetaxel followed by abiraterone, followed by enzalutamide, D-A-E; n = 14 cohorts) [63][64][65][66][67][68][69][70][71][72][73][74][75][76]. Rates of ≥50% PSA decline data were available for the majority of D-A-E cohorts (n = 13) and were highly variable, ranging from 12% to 40%.…”
Section: Prognostic and Predictive Clinical Factors And Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 16 retrospective cohort analyses assessed the effectiveness of a second ARAT therapy after progression on prior docetaxel and ARAT treatment (Table 2) [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Enzalutamide was the most investigated agent in this setting (docetaxel followed by abiraterone, followed by enzalutamide, D-A-E; n = 14 cohorts) [63][64][65][66][67][68][69][70][71][72][73][74][75][76]. Rates of ≥50% PSA decline data were available for the majority of D-A-E cohorts (n = 13) and were highly variable, ranging from 12% to 40%.…”
Section: Prognostic and Predictive Clinical Factors And Modelsmentioning
confidence: 99%
“…Rates of ≥50% PSA decline data were available for the majority of D-A-E cohorts (n = 13) and were highly variable, ranging from 12% to 40%. Median PFS for third-line enzalutamide ranged from 2.8 to 4.9 months (n = 7 cohorts) [63,65,66,[68][69][70]72], while median OS outcomes ranged from 4.8 to 10.6 months (n = 6 cohorts) [63,66,68,71,73,74]. Abiraterone outcomes in this setting were examined in only two studies (docetaxel followed by enzalutamide, followed by abiraterone, D-E-A) [77,78], with rates of ≥50% PSA decline of 4% and 8%, respectively.…”
Section: Prognostic and Predictive Clinical Factors And Modelsmentioning
confidence: 99%
“…For treatment sequences involving enzalutamide or abiraterone as a second-line agent following the opposite agent, several other studies have reported that 17-28% of patients achieved a PSA response. [26][27][28][29][30][31][32][33][34] A report from Schnadig et al showed that more patients reached a third-line treatment if they received docetaxel followed immediately by cabazitaxel, compared to docetaxel followed by abiraterone. 35 This retrospective analysis in 667 post-docetaxel mCRPC patients showed that 31% of patients who received cabazitaxel second-line received abiraterone in third-line, compared to only 12% of patients who received cabazitaxel third-line if they received abiraterone second-line.…”
mentioning
confidence: 99%
“…Of these, 3 original articles and 7 abstracts were selected for inclusion in this pooled analysis ( Figure 1 and Table 1). 11,12,[14][15][16][17][18][19][20][21] The primary outcomes were > 50% PSA RR, activity according to previous AA response, and median PFS (or TTP). The secondary outcome was safety and the median duration of treatment.…”
Section: Resultsmentioning
confidence: 99%